2016
DOI: 10.1038/srep21003
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Temperature, Heart Rate and Blood Pressure in Chinese Adults: Effect Modification by Individual Characteristics

Abstract: We collected data from Kailuan cohort study from 2006 to 2011 to examine whether short-term effects of ambient temperature on heart rate (HR) and blood pressure (BP) are non-linear or linear, and their potential modifying factors. The HR, BP and individual information, including basic characteristics, life style, socio-economic characteristics and other characteristics, were collected for each participant. Daily mean temperature and relative humidity were collected. A regression model was used to evaluate asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 31 publications
1
35
1
Order By: Relevance
“…These factors could increase susceptibility to infection and can also affect ILI surveillance. A study found that RHR is higher at very cold or hot temperatures 28 and heart rate can also be elevated when someone is dehydrated, which could be more likely to happen during certain seasons. Additionally, people might be less active during colder, winter months, resulting in deconditioning and increased heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…These factors could increase susceptibility to infection and can also affect ILI surveillance. A study found that RHR is higher at very cold or hot temperatures 28 and heart rate can also be elevated when someone is dehydrated, which could be more likely to happen during certain seasons. Additionally, people might be less active during colder, winter months, resulting in deconditioning and increased heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the higher the intensity (temperature) or the longer the duration of the heat wave, the more work required of the cardiovascular system to maintain normal temperature. Therefore, more intense or longer heat waves are thought to have greater health impacts ( Li et al 2016 ; Madaniyazi et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, since temperature variation may occur both indoors and outdoors, a few studies found that ownership and usage of air conditioning might reduce the effects of temperature on some health outcomes [ 43 , 44 ]. In addition, a large difference between outdoor and indoor temperature may have short-term impact on heart rate and blood pressure [ 45 ]. We did not analyze the potentially confounding effect of air conditioning and the effect of indoor-outdoor temperature differences due to the lack of necessary data, which suggests research directions for another future in-depth study.…”
Section: Discussionmentioning
confidence: 99%